"Can I take responsibility for bringing a person to this world who will be part of the apocalypse!?": Ideological dilemmas and concerns for future well-being when bringing the climate crisis into reproductive decision-making. (June 2022) - Bodin, Maja; Björklund, Jenny
Abstract: In the wake of the ongoing climate crisis and its negative effects on public health, it has been questioned by climate activists whether it is right to bring more children into the world. Moreover, according to previous scholarship, having one fewer child is the most high-impact lifestyle change individuals in developed countries can make in order to reduce greenhouse gas emissions. But do climate awareness and recommendations to have fewer children have any impact on how lay people reason around reproductive decision-making? In this paper, which is based on focus group discussions with people from different generations, we show how various and sometimes conflicting discourses on reproductive norms and responsibility are negotiated. Even though participants were highly aware of the ongoing discussions around the climate crisis, in the end it had little bearing on their decision to have children or not, and they justified reproduction through addressing other ways to contribute to a better world. Highlights: Participants were aware of the climate crisis, and many worried about climate change. Global crises did not have major impact on their decisions to have children or not. Participants found other ways of contributing to a better world. Some considered having fewer children than desired to reduce their carbon footprint. Environmental concerns related to reproduction could be traced back to the 1960s.